Nghiên cứu hoàn thiện qui trình nuôi trồng nấm hầu thủ Hericium Erinaceum - Lê, Viết Ngọc (Trường Đại học Đà Lạt, 2013)
The Monkey's Head Fungus Hericium erinaceum (Bull.: F r. ) Pers. has been cultivated in Lam Dong province. Ho Chi Minh city, and neighbouring regions on lager and lager scale.Nevertheless, the havested efficiency had been quite low because cultivators roughly knew about physilogical and ecological property of its. Consequently,I and my colleagues have been researched and defined out the growth rate of mecylia, the formation and development of fruitbodies of Monkey's Head Fungus . We had found out the acenic culture and corny media for which preserving primary strains and supplying secondry strains for farms of mushroom cultivation. We had also found out formula for mixturing substrates to cultivate Monkey's Head Fungus. Besides. Weprovied of effect of temperature, hydric, light, pH factors on growth and development of Monkey's Head Fungus. Data in this study. We estalished the complete process of Monkey' Head Fungus cultivation to provide higher productivity and better quality of Monkey's Head Fungus for food and medical industries for purposiving economic interests and health of community.